Performance of externally bonded fiber-reinforced polymer retrofits in the 2018 Cook Inlet Earthquake in Anchorage, Alaska. Issue 4 (November 2021) - Tatar, Jovan; Sattar, Siamak; Goodwin, David; Milev, Sandra; Ahmed, Shafique; Dukes, Jazalyn; Segura, Christopher
As part of the effort to improve the seismic performance of buildings in Alaska (AK), many of the deficient structures in Anchorage, AK, were retrofitted—some with externally bonded fiber-reinforced polymer (EBFRP) composite systems. The 2018 magnitude 7.1 Cook Inlet earthquake that impacted the same region offered an opportunity to evaluate the performance of EBFRP retrofits in a relatively high-intensity earthquake. This study summarizes the following findings of this field investigation: (1) the performance of EBFRP-retrofitted structures in the Cook Inlet earthquake and (2) the observations concerning the condition of FRP retrofits from over a decade of exposure in a subarctic environment. A deployment team from the National Institute of Standards and Technology (NIST) in collaboration with the University of Delaware (UD) Center for Composite Materials conducted post-earthquake inspections of EBFRP retrofits in multiple buildings to assess their performance during the earthquake and condition with respect to weathering. EBFRP debonding was documented with infrared thermography and acoustic sounding and the bond quality between EBFRP and concrete was assessed using pull-off tests. Visual inspections showed no major signs of earthquake damage in the EBFRP-retrofitted components. However, evaluation of debonding and pull-off test results suggested that outdoor conditions may have led to bond deterioration between EBFRP and concrete from installation defects that grew over time, freeze–thaw expansion from moisture present at the FRP/concrete interface, differences in thermal expansion of the materials, or a combination thereof. The carbon fiber–reinforced polymer (CFRP) bond to concrete was found to be more vulnerable to outdoor exposure than the glass fiber–reinforced polymer (GFRP) bond. Earthquake effects on FRP/concrete bond could not be assessed due to the lack of baseline data.